Baseplate Component TssK and Spatio-Temporal Assembly of T6SS in Pseudomonas aeruginosa - Liebl, David; Robert-Genthon, Mylène; Job, Viviana; Cogoni, Valentina; Attrée, Ina (Frontiers in Microbiology, 2019)
The Gram-negative bacteria use the contractile multi-molecular structure, called the Type VI Secretion System (T6SS) to inject toxic products into eukaryotic and prokaryotic cells. In this study, we use fluorescent protein fusions and time-lapse microscopy imaging to study the assembly dynamics of the baseplate protein TssK in Pseudomonas aeruginosa T6SS. TssK formed transient higher-order structures that correlated with dynamics of sheath component TssB. Assembly of peri-membrane TssK structures occurred de novo upon contact with competing bacteria. We show that this assembly required presence of TagQ-TagR envelope sensors, activity of PpkA kinase and anchoring to the inner membrane via TssM. Disassembly and repositioning of TssK component was dependent on PppA phosphatase and indispensable for repositioning and deployment of the entire contractile apparatus towards a new target cell. Finally, we also show that TssE is necessary for correct elongation and stability of TssB-sheath, but not for TssK assembly. Therefore, in P. aeruginosa, assembly of the TssK-containing structure relays on the post-translational regulatory envelope module and acts as spatio-temporal marker for further recruitment and subsequent assembly of the contractile apparatus.